Insight on the western Mediterranean crustal structure from GOCE satellite gravity data. (February 2019) - Dufréchou, G.; Martin, R.; Bonvalot, S.; Bruinsma, S.
Highlights: GOCE gravity allows to study crustal architecture in West Mediterranean complex tectonic setting. Sinistral or normal-sense displacement may occur between Corsica and Sardinia. Two unknown gravity anomalies are identified in the western Mediterranean basin. Abstract: GOCE-derived gravity anomalies are analyzed over the western Mediterranean in order to evaluate the information brings by these satellite observations on the complex lithospheric structure of this region. Free-air and Bouguer anomalies deduced from the latest GOCE model are analyzed and compared with the theoretical response computed from the CRUST1.0 and EPcrust models. Semi-quantitative and qualitative approaches are performed to highlight major geological domains and discontinuities. We show that GOCE gravity anomalies in Western Mediterranean are mainly caused by the thickness of the crust. We also observe two GOCE gravity anomalies located in the centre of the Mediterranean basin that could be related to ocean spreading process, but their nature is unclear and an inhomogeneity of the GOCE gravity response of continental shelves that are not explain by regional 3D models. Our analyses also suggest the presence of two major regional crustal-scale North-East-trending lineament in the western Mediterranean: the well-known North Balearic transform zone and the Cassidaigne-Asinara lineament that separates the Sardinia and Corsica blocks. This later lineament is associated with an apparent sinistral offset of gravity anomalies in the western Mediterranean suggesting strike-slip displacement during opening of the Mediteranean basin. A normal-sense displacement along the Cassidaigne-Asinara lineament between Corsica and Sardinia is alternatively proposed and could be more consistent with geodynamic reconstructions from previous tectonic and paleomagnetic studies. Although additional local geological and geophysical investigations are required to establish the possible separation of Corsica and Sardinia, the homogeneous observations provided by GOCE on both terrestrial and marine areas brings new views on lithospheric scale structure and evolution of this region.